MRI and pathology correlations in the medulla in sudden unexpected death in epilepsy (SUDEP): a postmortem study. (15th July 2020) - Patodia, S.; Tachrount, M.; Somani, A.; Scheffer, I.; Yousry, T.; Golay, X.; Sisodiya, S. M.; Thom, M.
Abstract : Aims: Sudden unexpected death in epilepsy (SUDEP) likely arises as a result of autonomic dysfunction around the time of a seizure. In vivo MRI studies report volume reduction in the medulla and other brainstem autonomic regions. Our aim, in a pathology series, is to correlate regional quantitative features on 9.4T MRI with pathology measures in medullary regions. Methods: Forty‐seven medullae from 18 SUDEP, 18 nonepilepsy controls and 11 epilepsy controls were studied. In 16 cases, representing all three groups, ex vivo 9.4T MRI of the brainstem was carried out. Five regions of interest (ROI) were delineated, including the reticular formation zone (RtZ), and actual and relative volumes (RV), as well as T1, T2, T2* and magnetization transfer ratio (MTR) measurements were evaluated on MRI. On serial sections, actual and RV estimates using Cavalieri stereological method and immunolabelling indices for myelin basic protein, synaptophysin and Microtubule associated protein 2 (MAP2) were carried out in similar ROI. Results: Lower relative RtZ volumes in the rostral medulla but higher actual volumes in the caudal medulla were observed in SUDEP ( P  < 0.05). No differences between groups for T1, T2, T2* and MTR values in any region was seen but a positive correlation between T1 values and MAP2 labelling index in RtZ ( P  < 0.05). Significantly lower MAP2 LI were noted in the rostral medulla RtZ in epilepsy cases ( P  < 0.05). Conclusions: Rostro‐caudal alterations of medullary volume in SUDEP localize with regions containing respiratory regulatory nuclei. They may represent seizure‐related alterations, relevant to the pathophysiology of SUDEP.